The optimisation and scale-up of microalgae cultivation for high level oil content for biodiesel - Ding, Gong Tao (2011)
Biodiesel is the mono-alkyl ester of long-chain fatty acids derived from renewable feedstock. It is one of the most renewable fuels that is also non-toxic and biodegradable. The microalgae biomass with high oil content is significant as a sustainable resource for biodiesel production. Production of biodiesel using microalgae biomass appears to be a viable alternative because there is no conflict with food supply compared with the first generation biofuels, such as oil crops and animal fat. This thesis deals with the optimisation of the levels of the variables pH and concentration of ferric chloride for harvesting marine microalgae by flocculation, marine microalgae wild strains limited selection for high level of oil, optimisation of biomass growth and oil content in aseptic sparged flasks, and scale-up of marine microalgae cultivation from flasks to non-aseptic tubular photobioreactor based on the attainment of turbulent flow at both scales. The 22 Factorial Design and the Method of the Path of Steepest Ascent are used in the optimisation of the levels of the variables for harvesting microalgae by flocculation. Sedimentation efficiency would reach to the top 99% when the volume of added ferric chloride solution (concentration 1 mol/L) is 0.44ml per litre and pH value is 8.45. For the microalgae wild strains limited selection, Tetraselmis sp, Nannochloropsis Palau Sara, Nannochloropsis Somalia, Nannochloropsis sp, Chlorella sp, Chetoceros sp strains of microalgae are cultivated aseptically in sea water at the same conditions for 7 days, the biomass are collected and lipid content are measured with GC-MS (Gas Chromatography-Mass Spectrometer Detector). The result shows that Nannochloropsis sp give the highest lipid content of 6.32 mg/L. In the optimisation of biomass growth and oil content in aseptic sparged flasks experiments, the 23 Factorial Design is used to investigate the effects of the variables nitrogen and phosphorus concentrations, % (v/v) of CO2 in the sparging air mixture, and illumination intensity. The Factorial Experiments at the area containing the maximum biomass concentration are complemented with the Composite Design. Analysis of the Response Surface indicated that at the theoretical point of maximum biomass concentration nitrogen and phosphorus concentration (N+P) are at 71.3+4.75mg/L, % (v/v) of CO2 is at 0.98% and illumination intensity (L) is at 781.25 lx, with the predicted biomass concentration at 143.09 mg/L. Experiments conducted at these optimised levels of experimental variables gave the biomass concentration of 136.67 mg/L and lipid concentration of 2.99 mg/L. In the scale-up of marine microalgae cultivation, marine microalgae are grown non-aseptically in the tubular photobioreactor which consisted of a vertical air-lift and a horizontal receiver. At the same light intensity and with the culture in turbulent flow resulting from sparging at 4.0L/min with air, and sparging with 1% (v/v) of CO2, a biomass concentration of 155 mg/L and a lipid content of 3.15 mg/L were achieved. This non-aseptically grown marine microalgae biomass will be used as the inoculum for a future large-scale open raceway pond cultivation of the marine microalgae grown on sewage-contaminated sea water sparged with industrial waste CO2